Potensi Sensor Kelembaban Tanah YL-69 Sebagai Pemonitor Tingkat Kelembaban Media Tanam Palawija - Saleh Yaakub; Rezagi Meilano (LPPM Politeknik Jambi, 2019)
Technology development can support various aspects of life including the agricultural sector. It is undeniable that the selection of good seeds and good plant maintenance, such as agricultural integration. Agricultural integration consists of good tillage and regular irrigation. Chili plants have very poor growth. To grow well, chili plants must have air content in a balanced tanaha.This final project discusses the control of soil moisture in chili plants. In this final project is made a tool for controlling soil moisture and automatic watering plants. Air pump as a sprinkler of chilli plants. This chili plant sprinkling system automatically adjusts the soil moisture conditions observed. To see the results of monitoring consistently can be seen on the LCD display.